Effects of methadone, buprenorphine, and naltrexone on actigraphy-based sleep-like parameters in male rhesus monkeys. (December 2022) - Berro, Lais F.; Zamarripa, C. Austin; Talley, Joseph T.; Freeman, Kevin B.; Rowlett, James K.
Highlights: This study evaluated actigraphy-based sleep parameters in adult male rhesus monkeys. Morning/evening treatments with methadone or buprenorphine impaired sleep. The effects of buprenorphine on sleep resulted in a biphasic dose–response function. Buprenorphine induced a much more robust sleep impairment compared to methadone. Evening treatment with naltrexone improved sleep-like measures. Abstract: Opioid use disorder (OUD) has been associated with the emergence of sleep disturbances. Although effective treatments for OUD exist, evidence suggests that these treatments also may be associated with sleep impairment. The extent to which these effects are an effect of OUD treatment or a result of chronic opioid use remains unknown. We investigated the acute effects of methadone, buprenorphine, and naltrexone on actigraphy-based sleep-like parameters in non-opioid-dependent male rhesus monkeys ( Macaca mulatta, n = 5). Subjects were fitted with actigraphy monitors attached to primate collars to measure sleep-like parameters. Actigraphy recordings were conducted under baseline conditions, or following acute injections of vehicle, methadone (0.03–1.0 mg/kg, i.m.), buprenorphine (0.01–1.0 mg/kg, i.m.), or naltrexone (0.03–1.0 mg/kg, i.m.) in the morning (4 h after "lights on") or in the evening (1.5 h before "lights off"). Morning and evening treatments with methadone or buprenorphine significantly increased sleep latency and decreased sleep efficiency. The effects of buprenorphine on sleep-like measures resulted in a biphasic dose–response function, with the highest doses not disrupting actigraphy-based sleep. Buprenorphine induced a much more robust increase in sleep latency and decrease in sleep efficiency compared to methadone, particularly with evening administration, and detrimental effects of buprenorphine on sleep-like measures were observed up to 25.5 h after drug injection. Treatment with naltrexone, on the other hand, significantly improved sleep-like measures, with evening treatments improving both sleep latency and sleep efficiency. The currently available pharmacotherapies for OUD significantly alter sleep-like parameters in non-opioid-dependent monkeys, and opioid-dependent mechanisms may play a significant role in sleep-wake regulation.